Audit Sistem Informasi Absensi Karyawan Berbasis Cobit 4.1 - Nadila Ayudiapasa; Pujiani Pujiani; Ratna Cantika (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2024)
Employee attendance information systems are an important component in human resource (HR) management in various organizations. Auditing attendance system information is necessary to ensure that the system runs effectively and efficiently, and complies with applicable regulations and policies. COBIT 4.1 (Control Objectives for Information and Associated Technologies) is an audit framework that can be used to deploy attendance information systems. This research aims to conduct an audit of the employee attendance information system using the COBIT 4 framework. This audit was carried out to evaluate the effectiveness of internal control, compliance with regulations, and operational efficiency of the employee attendance information system at XYZ company. The research method used is a combination of qualitative and quantitative, including interviews, observation and testing. The research results show that in general the employee attendance information system has been running well, but there are still several findings related to control and compliance weaknesses that need to be improved. The recommendations provided include improving access rights management, monitoring activities, as well as improving procedures and documentation.